Analysis Problems of Geography Teachers in Applying Learning Strategies to Sensing Material Far away at SMA N 7 Medan - Khairunnisa, Khairunnisa; Ermas Simaremare; Novita Annisah Hasibuan; Girang Stevani Bancin; Tondang Raja Purba (Jurnal Multidisiplin Sahombu, 2024)
This study aims to analyze the problems faced by geography teachers when implementing learning strategies with remote sensing tools. The research method used is descriptive and qualitative with a case study approach in a number of high schools. Data were collected through interviews, observations, and document analysis. According to the study, the main obstacles for teachers are the lack of appropriate learning materials, the lack of personnel skilled in remote sensing technology, and low motivation to learn materials that are considered complex. Suggested solutions include developing technology-based teaching materials, regular teacher training, and using a contextual approach to improve student understanding. The results of the study showed several problems, including limited access to supporting technology tools such as computers and remote monitoring software, lack of training for teachers on the latest technology, and low student interest in this material. In addition, some teachers have difficulty connecting theoretical concepts with appropriate field practices. Another factor that also influences is the lack of support from schools in providing adequate facilities.